Formaldehyde--a rapid and reversible inhibitor of hydrogen production by [FeFe]-hydrogenases. - Wait, A; Brandmayr, C; Stripp, S; Cavazza, C; Fontecilla-Camps, J; Happe, T; Armstrong, F (2011)
Dihydrogen (H(2)) production by [FeFe]-hydrogenases is strongly inhibited by formaldehyde (methanal) in a reaction that is rapid, reversible, and specific to this type of hydrogenase. This discovery, using three [FeFe]-hydrogenases that are homologous about the active site but otherwise structurally distinct, was made by protein film electrochemistry, which measures the activity (as electrical current) of enzymes immobilized on an electrode; importantly, the inhibitor can be removed after addition. Formaldehyde causes rapid loss of proton reduction activity which is restored when the solution is exchanged. Inhibition is confirmed by conventional solution assays. The effect depends strongly on the direction of catalysis: inhibition of H(2) oxidation is much weaker than for H(2) production, and formaldehyde also protects against CO and O(2) inactivation. By contrast, inhibition of [NiFe]-hydrogenases is weak. The results strongly suggest that formaldehyde binds at, or close to, the active site of [FeFe]-hydrogenases at a site unique to this class of enzyme--highly conserved lysine and cysteine residues, the bridgehead atom of the dithiolate ligand, or the reduced Fe(d) that is the focal center of catalysis.